Diabetes Mellitus and Depression: A Literature Review - Muhammad Novran Chalik (HM Publisher, 2022)
Diabetes Mellitus is a long-term condition characterized by excessive glucose or blood sugar levels. Diabetes mellitus (DM) type 2 patients are at a greater risk of developing depression. Diabetes mellitus causes vascular damage, particularly brain vascularity, which is linked to depression symptoms. Other than that, depression in diabetic patients is linked to poor blood sugar control, the family's lack of motivation to be concerned about diabetic complications The situation will create a vicious spiral that will exacerbate diabetes and sadness.